Effects of ozonation on cooling water systems - Mosugelo, Keneetswe Lilian (My University, 2010)
Cooling water systems are needed to dissipate heat. The mist from open system cooling towers has been implicated as a source of infections of Legionella pneumophila. As a result biocide is added to cooling water systems, but the addition of biocide worsens biofouling, scaling and corrosion. Increasing environmental pressure has resulted in a move away from biocides which are usually chlorine based chemicals, so that the use of ozone instead has recently been reported as a way of controlling microbiological growth. This study aims to compare the corrosion rates (using calculated and measured surface areas) of different metals exposed to chemically treated and ozone treated cooling water in an industrial cooling water system. The types of corrosion were also observed and recorded. The scales from different components of the cooling systems as well as scale from chemically and ozone treated D tower water were characterized qualitatively using X-ray diffraction (XRD), Thermo gravimetric Analysis (TGA) and Atomic Absorption Spectroscopy. The D tower is a cooling water circuit in which the cooling water is from the Vaal River. As expected, the stainless steel has the lowest corrosion rate of 0.000 milli inches/year followed by brass with 1.531 milli inches/year and lastly mild steel (2.098 milli inches/year). Water quality rather than the presence or absence of ozone determines the corrosion rate. This confirms the findings reported in the literature. Scale from chemically treated water contains many different compounds while scale from ozone treated contains only different polymorphs of CaCO3, which is present in the water source and magnesium calcite.
Keywords: Cooling water system; Ozone; Biocides; Biofouling; Corrosion rate; X-ray diffraction; Thermo gravimetric analysis